Human Amniotic Mesenchymal Stem Cells Promote Endogenous Bone Regeneration - Li, Jin; Zhou, Zhixuan; Wen, Jin; Jiang, Fei; Xia, Yang (Frontiers in Endocrinology, 2020)
Bone regeneration has become a research hotspot and therapeutic target in the field of bone and joint medicine. Stem cell-based therapy, aiming to promote endogenous regeneration, could greatly improve therapeutic effects and decrease side-effects of traditional reconstruction of large bone defects and disorders. Human amniotic mesenchymal stem cells (hAMSCs), as a kind of seed cells, have superior paracrine functions on immune-regulation, anti-inflammation and vascularized tissue regeneration. In this review, we summarized the source and characteristics of hAMSCs and analyzed their roles in promoting tissue regeneration. We reviewed the therapeutic effects and mechanisms of hAMSCs in promoting bone regeneration on two mainly aspects: joint diseases and bone defects. Finally, we analyzed the clinical application of hAMSCs from current clinical trials. Although more studies are needed to confirm hAMSCs could serve as bioactive drugs to treat bone diseases, it is undeniable that hAMSCs will have a good clinical application prospect.